1988
DOI: 10.1080/09670878809371263
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some fungicides and antibiotics against fungal and bacterial pathogens of betelvine (Piper betleL.)

Abstract: Five fungicides, 2 antibiotics and 2 combinations of fungicides and antibiotics were evaluated against incidence of bacterial and fungal diseases of Piper betle L. Cv. 'Desawari'. Copper oxychloride 50 WP (Blitox-50) at 0.25% at 15 days interval was most effective against mortality caused by Phytophthora parasitica var. piperina Dastur; whereas 0.25% Copper oxychloride 50 WP with 500 ppm streptocycline was best against leaf spots caused by Xanthomonas campestris pv. betlicola Dye. and Colletotrichum capsici Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In certain areas, identical betel plants are grown under various names, while in other regions, distinct betel plants share identical names. As a result, varieties carry the prefix 'Desi' in their names [8]. Hence, it is consistently challenging to distinguish between varieties, often labelled with local names by the farmers.…”
Section: Introductionmentioning
confidence: 99%
“…In certain areas, identical betel plants are grown under various names, while in other regions, distinct betel plants share identical names. As a result, varieties carry the prefix 'Desi' in their names [8]. Hence, it is consistently challenging to distinguish between varieties, often labelled with local names by the farmers.…”
Section: Introductionmentioning
confidence: 99%
“…No extensive systematic studies on characterizing these landraces have been made in the past. Some work on the essential oil has shown that most of the PB landraces fall into five broad groups, Bangla, Kapoori, Khasi, Sanchi and Meetha [4]. Studies conducted on molecular taxonomy using random amplified polymorphic DNA (RAPD) using seventy landraces have also shown the existence of major groups as Bangla, Kapoori and others [5,6].…”
mentioning
confidence: 99%
“…The chemical constituents of betel essential oil consist mainly of terpenes and phenols [4], and the characteristic flavor of betel is due to phenols. The terpenoids include 1,8-cineole,cadinene, camphene, caryophyllene, limonene, and pinene.…”
mentioning
confidence: 99%